Surface electric fields and impedance matrix elements of stratified media. - Leung Tsang (IEEE Transactions on antennas and propagation)
For the various geometrical configurations of waves in stratified media, we consider the important case when both source and field points are located on the same interface separating two different dielectric media. We denote this configuration as surface electric field case. In this paper, the electric fields are calculated numerically without using potentials. For the surface electric field case the integrand of the electric field grows with kρ3/2 for large κρ making the Sommerfeld integral singular. To calculate the surface electric fields in the spatial domain, we previously applied a technique of higher order asymptotic extraction. In the higher order asymptotic extraction, the higher order asymptotic parts were calculated analytically. The remainder, which has an integrand decays as κρ-3/2 was calculated numerically along the Sommerfeld contour path of integration. In this paper, we use a different extraction technique, the half-space extraction. After the half-space extraction, the integrand of the Sommerfeld integral of stratified media decays exponentially and the integral is calculated along the Sommerfeld integration path. The half-space extraction part is calculated by numerical integration along the vertical branch cuts. The surface electric fields for stratified media using half-space extraction and higher order asymptotic extraction are in good agreement. To validate the accuracy of the solution, we also compute the impedance matrix elements using surface electric fields, testing, and basis functions all in the spatial domain. The results are then compared with the results of the spectral domain method. The comparisons of the complex impedance matrix elements are tabulated and show that the difference is less than 2%